Correlative scanning and transmission electron microscopic study on the ependymal surface of Cebus apella - Cáudio A. Ferraz de Carvalho; II-Sei Watanabe; Romeu Rodrigues de Souza (Arquivos de Neuro-Psiquiatria)
Topographical variations of the ependymal surface of the whole brain ventricular system of Cebus apella, a wild Brazilian species, were studied at the scanning electron microscope after C02 critical point drying and carbon-gold coating. Certain selected areas were also studied at the transmission electron microscope, following standard technical procedures. We observed distinct patterns in the distribution of cilia, microvilli, other cell projections, and the so called supraependymal structures. Based on the morphological findings, functional considerations are made.